Batik for the future: The crucial role of digital leadership in the batik Industry Ciwaringin, Indonesia - Dini Selasi; Cory Vidiati; Ahmad Rofik (Journal of Islamic, Social, Economics and Development, 2024)
Digital leaders ensure sustainable practices in accordance with the demands of today's consumers in the batik industry who are increasingly aware of ethics and products that have global standards. Digital automation as a way to adopt digital technology in the batik industry in Batik Ciwaringin is unfortunately still not maximized in its use, especially for marketing expansion. The purpose of this study is to identify digital leadership, the implementation of marketing strategies carried out by digital leadership. Qualitative research methodology, data and data sources; primary data and secondary data, data collection techniques; in-depth interviews and documentation studies, data analysis; SWOT analysis and content analysis to identify data collected from interviews and documents. The results of this study are identifying digital leadership; having a clear vision, having digital skills, the ability to apply technology for marketing, focus on consumers. Digital leadership and the level of batik products must include aspects of management, technology and creativity in the batik industry. The need to implement a digital business strategy that is influenced by digital leadership.